Trade unions and technological change : a research report submitted to the 1966 Congress of Landorganisationen i Sverige (the Swedish Confederation of Trade Unions) - Anderman, Steven D.; Landorganisationen i Sverige (London : Allen & Unwin, 1967)
This research report by the Swedish Confederation of Trade Unions, or LO as it is popularly known, constitutes one of the first major attempts by a trade union, employer or government group in a country experiencing sustained full employment and widespread scarcity of labour to examine systematically the manpower problems associated with rapidly changing technology.
Edited and translated by Anderman, S. D. staff tutor in industrial relations, university of Oxford, delegacy for extra-mural studies.
Bibliographical footnotes.
rpm 14/03/2018
Loans
Keywords: Automation; Trade unions; Trade unions; Technological change; Sweden